Toré potiguara: relações entre o rito e as práticas pedagógicas no ensino de arte - Silva, Rafael Sabino da (2024)
This research deals with an investigation process based on the elements constituted in the ritual of the TORÉ DO POVO POTIGUARA DA PARAÍBA, with the objective of establishing dialogues between the ritual practice of Toré Potiguara and research into dance, based on the experiences of the people investigated during the process. The research seeks to highlight the experience and strengthening of the Potiguara indigenous culture in the school context, where there is still a void in relation to this culture. To this end, the development of this theme, which addresses dance, art and culture of indigenous peoples, is necessary due to the struggle and resistance of the permanence of the identity of a people whose history is the basis of so many other Brazilian cultures. The Antônio Azevedo Municipal School, in the Municipality of Baía da Traição, on the North coast of Paraíba, was the field of investigation, in the 6th and 7th year Elementary School classes, with indigenous students of the Potiguara ethnic group, aged between 11 and 14 years. The project developed at this school seeks to offer classes on the elements of Toré Potiguara dance in an integrated way into the art curriculum. Through this practice, the aim is to deepen the cultural relationships that students carry in their bodies, through experience with Toré at school, through the development of methodologies, providing them with cultural, social and historical experiences of doing something artistic during the teaching and learning processes. To this end, this is a research with a qualitative approach, using questionnaires as tools, discussion between teachers and students, observation through speeches, interviews, field diary based on the teacher's observations and records of classes through videos and photographs. All of these instruments were used as a means of collecting data during the meetings in the research focus group.